Implementation of blended learning in fiqh learning at MIN 7 Boyolali - Khotimah, Kusnul; Junanto, Subar; Supriyanto, Supriyanto (Institute of Computer Science (IOCS), 2024)
The purpose of this study is to find out the implementation of blended learning in learning Fiqh at MIN 7 Boyolali, evaluate the obstacles that arise during implementation and find the right solution. The research method used descriptive qualitative. The research subjects were Fiqh teachers and fifth grade students of MIN 7 Boyolali. Data collection techniques using observation and interviews. Data analysis used the Miles and Huberman technique. The results showed that the implementation of blended learning in Fiqh learning in class V MIN 7 Boyolali can be an effective approach in improving students' understanding of Hajj material. The flexibility and accessibility of online materials are the advantages of blended learning. By combining face-to-face learning, students are more stable in receiving a comprehensive understanding. The obstacles in blended learning are uneven internet accessibility and different levels of digital literacy. The solution that can be taken by MIN 7 Boyolali is to improve internet access in the madrasa environment and conduct digital training for teachers and students. The contribution of this research is to fill the existing knowledge gap and provide practical guidelines for MIN 7 Boyolali and other MI in adopting a blended learning approach successfully in learning Fiqh.